2015
DOI: 10.1111/cge.12618
|View full text |Cite
|
Sign up to set email alerts
|

Measuring genetic knowledge: a brief survey instrument for adolescents and adults

Abstract: Basic knowledge of genetics is essential for understanding genetic testing and counseling. The lack of a written, English language, validated, published measure has limited our ability to evaluate genetic knowledge of patients and families. Here, we begin the psychometric analysis of a true/false genetic knowledge measure. The 18-item measure was completed by parents of children with congenital heart defects (CHD) (n=465) and adolescents and young adults with CHD (ages 15-25, n=196) with a mean total correct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…Researchers have begun to look at subcategories of genetic knowledge [13, 23, 24]. Some emerging categories have included basic physiology of genetics [24], applied knowledge of the relationship between genes, health, and disease [13, 24], the complex mechanisms underlying genetics [13, 23], and procedural/skills relating to genetics and health [23].…”
Section: Measures Of Genetic Knowledgementioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have begun to look at subcategories of genetic knowledge [13, 23, 24]. Some emerging categories have included basic physiology of genetics [24], applied knowledge of the relationship between genes, health, and disease [13, 24], the complex mechanisms underlying genetics [13, 23], and procedural/skills relating to genetics and health [23].…”
Section: Measures Of Genetic Knowledgementioning
confidence: 99%
“…Some emerging categories have included basic physiology of genetics [24], applied knowledge of the relationship between genes, health, and disease [13, 24], the complex mechanisms underlying genetics [13, 23], and procedural/skills relating to genetics and health [23]. A recent study by Fitzgerald-Butt et al [24] conducted a psychometric analysis on an updated version of 18 items often used within clinical groups in the genetic knowledge literature [25-27], first presented by Jallinoja and Aro [12]. Following the removal of two items that did not fit neatly into categories, two underlying latent factors were identified that mapped to categories labelled basic (e.g., characteristics of genes, chromosomes, and gene function) and applied (e.g., the relationship of genes, health and disease) knowledge about genetics.…”
Section: Measures Of Genetic Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…Erby, Roter, Larson, & Cho, 2008;Hooker et al, 2014;Hott et al, 2002;Molster, Charles, Samanek, & O'Leary, 2008;Pearson & Liu-Thompkins, 2012;Saul, 2013). They have also largely focused on well-defined populations such as undergraduate students and young adults (Carver et al, 2017;Fitzgerald-Butt et al, 2016). This research is limited, as it does not provide a comprehensive picture of genetic literacy in the population.…”
Section: Problem Statementmentioning
confidence: 99%